Pengelolaan Tanaman Jagung (Zea mays) di Tiga Desa Ogan Ilir Sumatera Selatan - Dani Dermawan Sinaga; Anisa U Rachel; Imillia Santika; Pitria P Rahayu; Muh A Rohman; Sihar Febryanto (xxxx-xxxx, 2023)
Sinaga DD, Rachel AU, Santika I, Rahayu PP, Rohman MA, Febryanto S. 2022. Management of corn plants (Zea mays) in three Ogan Ilir Villages, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 983-990. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Corn (Zea mays) is a commodity that is needed by the community as a source of food other than rice. The high demand for corn causes a lack of domestic production capacity. The purpose of this literature study is to examine the management system, types of varieties, and utilization of corn plants in three places, namely Timbangan, Palem Raya, and Tanjung Pering in Ogan Ilir, South Sumatra. The method used in this study uses descriptive data analysis and data collection and collection techniques by means of quantitative analysis such as surveys, interviews and documentation. Based on the results of interviews and surveys, farmers carry out various planting to harvesting and sales, ranging from the use of fertilizers, spacing, anticipation of pest attacks. The application of organic fertilizers and chemical fertilizers to sweet corn plants in each of the places we surveyed was different. Because the doses given by farmers are different, it must be in accordance with the levels required by the corn plant in order to produce good corn. From this research, it can be concluded that the strategies used by farmers in the process of planting to harvesting their produce are different, thus affecting the income they get. In increasing corn production, farmers need to pay attention to maintaining the growth of corn from seed to harvesting.